2016
DOI: 10.5812/iranjradiol.36849
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evaluation of the Biomechanical Properties of Optic Nerve and Peripapillary Structures by Ultrasonic Shear Wave Elastography in Glaucoma

Abstract: BackgroundPrimary open-angle glaucoma is a multifactorial serious disease characterized by progressive retinal ganglion cell death and loss of visual field.ObjectivesThe purposes of this study were to investigate shear wave elastography (SWE) use in the evaluation of the optic nerve (ON) and peripapillary structures, and to compare the findings between glaucomatous and control eyes.Patients and MethodsA case-controlled study, including 21 patients with primary open-angle glaucoma and 21 age-matched control sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 26 publications
1
22
1
1
Order By: Relevance
“…In addition, in a living rat model, Zha et al assessed the safety and feasibility of acoustic radiation force impulse elastography at a fixed high US pressure (MI of 1.6) and reported that it could be safely applied in human eyes. Recently, in the literature, elastographic studies have been performed for ocular and periocular tissues in human eyes, and there have been reported side effects . There were no changes in visual function before and after an SWE examination in the participants involved in the study.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, in a living rat model, Zha et al assessed the safety and feasibility of acoustic radiation force impulse elastography at a fixed high US pressure (MI of 1.6) and reported that it could be safely applied in human eyes. Recently, in the literature, elastographic studies have been performed for ocular and periocular tissues in human eyes, and there have been reported side effects . There were no changes in visual function before and after an SWE examination in the participants involved in the study.…”
Section: Discussionmentioning
confidence: 93%
“…However, we found only 3 studies in which elastography was used for the study of the optic nerve in glaucoma patients but none of these studies included subjects with PC [12,15,18]. Agladioglu et al compared the SROFRCS and optic disk/ optic nerve SR values obtained in glaucoma patients with a control group but found no statistically significant difference [18].…”
Section: Discussionmentioning
confidence: 98%
“…Agladioglu et al compared the SROFRCS and optic disk/ optic nerve SR values obtained in glaucoma patients with a control group but found no statistically significant difference [18]. Dikici et al detected higher elasticity values in the glaucoma group [12] and Unal et al found higher optic nerve elasticity values in the glaucoma group than the control group (in these two studies the Shear Wave Elastography [SWE] technique was used) [15]. We obtained similar results regarding the elasticity of the optic nerve in glaucomatous patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations